Changes in body composition and physical performance measures during a regular competitive season among young backs and forwards rugby players - Zabaloy, S.; González, J. G.; Giráldez, J.; Fink, B.; Alcaraz, P. E.; Pereira, L.; Loturco, I.; Freitas, T. T. (Sports Biomechanics, 2022)
This study aimed to compare the changes in body composition and physical qualities of under 19`s backs and forwards during the season (i.e. from pre-season [Pre-S] to end-season [End-S]). Twenty-seven male youth rugby union players (mean ± SD: age, Forwards [n = 11]: 17.5 ± 1.2 and Backs [n = 16]: 17.0 ± 0.9 years) participated in this study. Participants were tested twice (i.e. at Pre-S and End-S) and completed: anthropometric, body composition, countermovement and squat jumps, 30-m sprint, squat and bench press 1-repetition maximum (SQ-1RM and BP-1RM). Significant differences were observed between Pre-S and End-S for body mass (BM) and lean mass (LM), among both playing positions (p < 0.034; ES > 0.71), whereas all other variables remained unchanged. Regarding physical performance, backs and forwards showed greater SQ-1RM and BP-1RM, respectively (p < 0.043; ES>-0.69). Moreover, backs and forwards exhibited higher split times from 5 to 30 m (p: 0.013 to <0.001). Substantial increases were observed in BM and LM for backs and forwards, which may have negatively impacted acceleration (i.e. 5-m sprint time) and initial sprint momentum for both playing positions. Our findings highlight the importance of carefully balancing changes in BM and body composition, to avoiding the detrimental effects of these variations on sprint performance.